Child mortality, health expenditure and poverty in the western nations 1979–2010: Are English-speaking countries' children disadvantaged?. (February 2015) - Pritchard, Colin; Williams, Richard J; Wallace, Mark S
Child mortality rates (0–4 years) between 1979 and 2010 and poverty were shown to be significantly worse in five of the six English-speaking countries than in the other 15 western nations suggesting that in these countries children are relatively disadvantaged.